A Retrospective Analysis of Patients Presenting with Acute Hyperkalemia in an Emergency Care Setting - Zhang L; Sun P; Liu X; Yang Y; Sun RN; Wang XD (Dove Medical Press, 2024)
Lei Zhang,* Peng Sun,* Xin Liu, Ya Yang, Ruo-Nan Sun, Xu-Dong Wang Department of Emergency Medicine, Aerospace Center Hospital, Beijing, 100049, People's Republic of China*These authors contributed equally to this workCorrespondence: Xu-Dong Wang, Department of Emergency Medicine, Aerospace Center Hospital, 15 Yuquan Road, Haidian District, Beijing, 100049, People's Republic of China, Tel +86 01059975120, Email wxundong@126.comObjective: We aimed to analyze the clinical characteristics and prognostic factors of patients with severe hyperkalemia in the emergency department.Methods: This retrospective cohort study included adult patients diagnosed with severe hyperkalemia who sought medical care at the emergency department of Aerospace Center Hospital between January 2018 and May 2022. Clinical data, including demographics, comorbidities, laboratory findings, and outcomes, were systematically collected. Patients were categorized into survival and deceased groups based on in-hospital mortality. Comparative analysis between these groups identified significant differences, highlighting key clinically covariates. Binary logistic regression was employed to determine the primary factors influencing patient outcomes.Results: Of 90 patients diagnosed with severe hyperkalemia, 64 were in the survival group, and 26 in the deceased group. Binary logistic regression identified several significant predictors of mortality, including higher APACHE II scores (odds ratio [OR] 1.41, P = 0.02), widened QRS wave on electrocardiogram (ECG) (OR 79.39, P = 0.04), and elevated serum potassium levels (OR 1.3, P = 0.04). In contrast, emergency blood purification was associated with a reduced mortality rate (OR 0.29, P = 0.03).Conclusion: Key risk factors for mortality in patients with severe hyperkalemia include widened QRS wave on ECG, elevated APACHE II score, and high serum potassium level. Timely correction of hyperkalemia through emergency blood purification significantly improves patient outcomes.Keywords: clinical manifestation, prognosis, risk factors, severe hyperkalemia, treatment